Differences in travel behaviors of small and large cycling events participants - Rauter, Samo; Topič, Mojca Doupona (Applied Studies in Agribusiness and Commerce, 2013)
Tourism has been and will continue to be one of the biggest and most profitable industries in the world. Sport is obviously a very important aspect of society in many different ways: culturally, economically and socially. Like in the past, local authorities continue to regard all sporting events as a way of promoting and positioning their destination. Participation in sport events relates to tourism because it also involves travelling to host destinations. Therefore, the aim of our study is to compare participation in small and large sport-for-all events in relation to tourism in Slovenia. We analysed the factors determining differences in the travel behaviours of sport event participants and certain aspects of participation (travel behaviour, frequency of sport event participation, reasons for participation) at the largest cycling event in Slovenia (the Franja cycling marathon) and two smaller cycling events (the “Three hearts Radenci” recreational cycling marathon and the “Around the region of Prlekija” recreational cycling marathon). The study analysed the active participants of different cycling sport events. The sample of respondents consisted of 382 participants. We found that over the third of the participants take on the role of a sport tourist in their travels. They are also very sport-active in their leisure time. The majority of them are engaged in sport activities more than three times a week. The results indicate differences in travel behaviour and sport-active lifestyles among the participants of different types of small and larger sport events.